The vesicular-arbuscular (VA) mycorrhiza and its effects on growth of vegetatively propagated Theobroma cacao L. - Chulan, H. Azizah; Martin, K. (Kluwer Academic Publishers, 1992)
A greenhouse experiment was conducted to study the effects of mycorrhizal inoculation on growth and nutrient uptake of vegetatively propagated cocoa plants from the Sabah hybrid (NA 33 × PA 7) raised on unsterilized Munchong soils. Inoculation with mixed species of Scutellospora and Glomus, resulted in higher dry matter yield and stem diameter of mycorrhizal plants obtained through budding, air layering or marcotting (a form of asexual plant propagation using vegetative parts and the selection of a healthy branch and scraping off the bark at the lower end of the branch, forcing it to root by covering it with a ball of soil) and stem cutting. Budded and marcotted mycorrhizal plants gave a significant increase in P content of shoots. In contrast, only budded mycorrhizal plants (on both young and old rootstocks) gave a significantly higher Ca concentration in tops, compared to uninoculated plants. © 1992 Kluwer Academic Publishers.